Demand for courier services: determinants for customer organisations in a developing country. (2018) - Tiamiyu, Mutawakilu A.; Eigbe, Oserere E.
This study modelled the demand for courier services by customer organisations in a developing country, specifically Ibadan metropolis, Nigeria, using the price of service, customer organisation variables and variables from the SERVQUAL and logistics service quality models as predictors. PLUM ordinal regression analyses were performed on data collected with a validated questionnaire administered on 74 purposively and conveniently sampled customer organisations. All the courier services reported low demand and customer organisation size inversely predicted demand for human messenger services. However, organisation attitude to quality in operations and communications and the perceived value of couriered packages did not predict demand. Price inversely predicted demand for only NIPOST services (government-operated) and service quality variables predicted demand for most services. Customer organisation factors predicted demand for NIPOST services, while service factors predicted demand for some services. Nigerian courier services should build upon these findings to improve service quality to boost demand by customers.